Expression of Constitutive Fusion of Ubiquitin to PCNA Restores the Level of Immunoglobulin A/T Mutations During Somatic Hypermutation in the Ramos Cell Line - Lerner, Leticia K.; Bonte, Dorine; Le Guillou, Morwenna; Mohammad, Mahwish Mian; Kasraian, Zeinab; Sarasin, Alain; Despras, Emmanuelle; Aoufouchi, Said (Frontiers in Immunology, 2022)
Somatic hypermutation (SHM) of immunoglobulin (Ig) genes is a B cell-specific process required for the generation of specific and high-affinity antibodies during the maturation of the immune response against foreign antigens. This process depends on the activity of both activation-induced cytidine deaminase (AID) and several DNA repair factors. AID-dependent SHM creates the full spectrum of mutations in Ig variable (V) regions equally distributed at G/C and A/T bases. In most mammalian cells, deamination of deoxycytidine into uracil during S phase induces targeted G/C mutagenesis using either direct replication of uracils or TLS mediated bypass, however, only the machinery of activated B lymphocytes can generate A/T mutagenesis around AID-created uracils. The molecular mechanism behind the latter remains incompletely understood to date. However, the lack of a cellular model that reproduces both G/C and A/T mutation spectra constitutes the major hurdle to elucidating it. The few available B cell lines used thus far to study Ig SHM indeed undergo mainly G/C mutations, that make them inappropriate or of limited use. In this report, we show that in the Ramos cell line that undergoes constitutive G/C-biased SHM in culture, the low rate of A/T mutations is due to an imbalance in the ubiquitination/deubiquitination reaction of PCNA, with the deubiquitination reaction being predominant. The inhibition of the deubiquitinase complex USP1-UAF1 or the expression of the constitutive fusion of ubiquitin to PCNA provides the missing clue required for DNA polymerase  recruitment and thereafter the introduction of A/T base pair (bp) mutations during the process of IgV gene diversification. This study reports the establishment of the first modified human B cell line that recapitulates the mechanism of SHM of Ig genes in vitro.